If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -4y = 27 Solving 2x + -4y = 27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4y' to each side of the equation. 2x + -4y + 4y = 27 + 4y Combine like terms: -4y + 4y = 0 2x + 0 = 27 + 4y 2x = 27 + 4y Divide each side by '2'. x = 13.5 + 2y Simplifying x = 13.5 + 2y
| -2(7x-3x)=24 | | 3/4x=-1/2x^2+6 | | u/5+3=-5 | | x+(3/4)=4 | | 24-2=10 | | T=1/2c+6 | | 3x^2+8x-2=-7 | | 36x^2+134x+8= | | 5x+6y=9y-10 | | 3(x+2)+3(4-x)=-8 | | 2/x=x+4/x^2 | | 16=2c | | 2/3u-1=7/5u-7/5 | | 5y+10=12y+8 | | -4(3-12)= | | -3(5x-3x)=42 | | 198=82-u | | C=0.04t+6.9 | | x+.75=4 | | 5n+20=n | | 6n-1-2n=14 | | 4m+4=40 | | 227-y=156 | | -x+6=x+28 | | 8p=-56 | | 3+5x=-6x+14 | | 237=-v+76 | | 3(x-3)=8(4-2x) | | 6(2-7)= | | -4+4x=-3x-39 | | 5/2*5 | | 8y-5+5y=47 |